TWO POEMS BY ALEJANDRO ROMUALDO: RHETORIC-ARGUMENTATIVE ANALYSIS AND WORLD MODELS - Balceda Requena, Luis Fernando (2021)
The purpose of this article is to show which are the models of the world raised in two poems of Poesía concreta (1952) by Alejandro Romualdo. For this intent, we will develop a rhetorical-argumentative analysis based on Stefano Arduini's approach to figurative fields, in addition to other notions such as interlocutors, ethos and the argumentative techniques developed by Perelman. This analysis aims to demonstrate the persuasive power of Romualdo's poetic work, as he tries to convince readers, but also the performative desire of it in the sense that Manuel Asensi points out regarding world models; this to the extent that the Peruvian poet tries to openly intervene in the society that he represents in his poems.